BS EN 2213. Aerospace series. Steel 15CrMoV6 (1.7334). Air melted. Hardened and tempered. Bars. De ≤ 16 mm. 980 MPa ≤ Rm ≤ 1 180 MPa. (11th February 2021) - British Standards Institution,
No abstract available